Sensory anatomy of the most aquatic of carnivorans: The Antarctic Ross seal, and convergences with other mammals - Loza, Cleopatra Mara; Latimer, Ashley E.; Sánchez Villagra, Marcelo R.; Carlini, Alfredo Armando (Biology Letters)
Transitions to and from aquatic life involve transformations in sensory systems. The Ross seal, Ommatophoca rossii, offers the chance to investigate the cranio-sensory anatomy in the most aquatic of all seals. The use of non-invasive computed tomography on specimens of this rare animal reveals, relative to other species of phocids, a reduction in the diameters of the semicircular canals and the parafloccular volume. These features are independent of size effects. These transformations parallel those recorded in cetaceans, but these do not extend to other morphological features such as the reduction in eye muscles and the length of the neck, emphasizing the independence of some traits in convergent evolution to aquatic life. Fil: Loza, Cleopatra Mara. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Departamento Científico de Paleontología de Vertebrados; Argentina Fil: Latimer, Ashley E. Universität Zürich; Alemania Fil: Sánchez Villagra, Marcelo R. Universität Zürich; Alemania Fil: Carlini, Alfredo Armando. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Departamento Científico de Paleontología de Vertebrados; Argentina